Political Warfare : Strategies for Combating China's Plan to "Win without Fighting" - Gershaneck, Kerry K., 1953- (Book collections on Project MUSE., 2020)
"Political Warfare provides a well-researched and wide-ranging overview of the nature of the People's Republic of China (PRC) threat and the political warfare strategies, doctrines, and operational practices used by the Chinese Communist Party (CCP). The author offers detailed and illuminating case studies of PRC political warfare operations designed to undermine Thailand, a U.S. treaty ally, and Taiwan, a close friend"--